Characterization of Pineapple Peel Activated Carbon (Ananas comosus) as an Iron (Fe) Heavy Metal Adsorbent with NaOH and NH4OH Activators - Hasra, Putri Ramadani; Yangti, Ilda ilda; Gusti, Herdi Idriawien; Karneng, Syahdam (Universitas Nusa Cendana, 2025)
The purpose of this study was to investigate the effect of strong and weak base activators on the adsorption properties of activated carbon derived from pineapple peel waste. Activated carbon prepared with NaOH and NH₄OH activators exhibited different physical characteristics; NaOH-activated carbon appeared darker and had a rougher texture compared to NH₄OH-activated carbon. The NaOH-activated carbon contained a moisture content of 8.2%, an ash content of 2.22%, and an iodine adsorption capacity of 393.75%. In contrast, the NH₄OH-activated carbon contained a moisture content of 9.9%, an ash content of 2.68%, and an iodine adsorption capacity of 382.41%. Atomic absorption spectrophotometry (AAS) analysis showed an adsorption capacity of 0.17 mg/L for NaOH-activated carbon and 0.18 mg/L for NH₄OH-activated carbon. Fourier Transform Infrared (FTIR) spectroscopy revealed that NaOH-activated carbon contained O–H (hydroxyl), C=C (aromatic), C–H (alkane), C–O (alcohol), and C=H (alkene) functional groups, while NH₄OH-activated carbon exhibited O–H (hydroxyl), C=C (aromatic), C–H (alkane), and C=H (alkene) groups.